Performance Under Pressure: Unpacking Direct and Non-Mediated Effects of Empowerment, Job Involvement, and Commitment on Lecturer Performance - Tenrisau, Muhammad Akhsan; Syahnur, Muh. Haerdiansyah (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Private universities in South Sulawesi are striving to improve lecturer performance amid growing academic demands. This study addresses a research gap by examining how psychological empowerment, job involvement, affective commitment, and effort influence in-role performance. Based on 307 valid responses, the data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that psychological empowerment, job involvement, and affective commitment significantly affect in-role performance. Effort also contributes directly to performance and mediates the relationship between affective commitment and in-role performance. However, effort does not mediate the effects of psychological empowerment or job involvement. These findings enrich organizational behavior literature by highlighting the importance of psychological and behavioral factors—particularly empowerment, commitment, and effort—in enhancing academic staff performance in under-resourced higher education institutions.